Penggunaan Media Kartu Kata Bergambar Terhadap Kemampuan Membaca Permulaan pada Siswa Fase A SD Negeri 24 Temmalebba Kota Palopo (Indo-MathEdu Intellectuals Journal, 2025)
This study is based on the low initial reading ability of students caused by conventional learning methods and the lack of use of interesting media that are appropriate to the characteristics of children. This study aims to describe the use of picture word cards in improving initial reading ability in phase A students of SD Negeri 24 Temmalebba, Palopo City. This type of research is descriptive qualitative with a qualitative approach. The subjects of the study were teachers and phase A students of SD Negeri 24 Temmalebba, Palopo City. Data collection techniques were carried out through observation, interviews, tests, and documentation. Data analysis refers to data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of picture word cards can improve students' initial reading ability. Based on the test results, out of 28 students, there were 12 students (42.9%) in the very good category, 7 students (25%) in the good category, 5 students (17.9%) in the sufficient category, and 4 students (14.2%) in the less category, with an average overall score reaching 80% which is included in the very good category. Picture word cards can attract students' attention, foster their interest in learning, and help them recognize letters, syllables, and words more easily and enjoyably. Therefore, picture word cards are effective in improving early reading skills in Phase A students at SD Negeri 24 Temmalebba.